Giving Thanks at Thanksgiving Point - Nelson, Kari Ross (Museum and Society, 2020)
Even before the COVID-19 pandemic, the topic of self-care was trending in the museum field. In the thick of the pandemic, webinars from multiple museum-related professional associations featured discussion around the topic. Meditation, simplification, time outdoors, physical activity and 'unplugging' were commonly discussed practices. Seldom discussed, however, was the practice of gratitude. Current studies provide evidence of the benefits of gratitude to both emotional and physical health. While gratitude will not solve the challenges of a pandemic, at Thanksgiving Point we found tapping into the origins of our name to be a refreshing response to coping with them.